2021
DOI: 10.1109/access.2021.3106269
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Sparrow Search Algorithm Based on Constructing Similarity

Abstract: Sparrow search algorithm (SSA) is easy to fall into local convergence and convergence stagnation. In order to solve these problems, this paper introduced Circle chaos map into the original SSA to improve its global search ability at the beginning of iteration. Meanwhile, it introduced T-distribution variation to affect the sparrow population position update rules in different iteration periods. Finally, we constructed the ''similarity function'' to measure the ''dispersion'' of the sparrow population, and form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Jianhua and Zhiheng [ 19 ] worked on the local convergence and convergence stagnation of the original SSA. The Circle chaos map was used with the SSA, where the results showed that the model had a more vital global optimization ability and higher precision in convergence.…”
Section: Recent Variants Of Ssamentioning
confidence: 99%
“…Jianhua and Zhiheng [ 19 ] worked on the local convergence and convergence stagnation of the original SSA. The Circle chaos map was used with the SSA, where the results showed that the model had a more vital global optimization ability and higher precision in convergence.…”
Section: Recent Variants Of Ssamentioning
confidence: 99%
“…Mechanical optimization problem is closely related to mathematical model. [51,52] The key of constructing optimal design mathematical model is to find design variables, objective functions, and constraints. This section uses HMSWHO to optimize three mechanical design problems, which are tensile/ compression spring design problem (case 1), welded beam design problem (case 2), and pressure vessel design problem (case 3).…”
Section: Optimization Of Mechanical Designmentioning
confidence: 99%
“…Set the population size to N , dimension of the solution space to D , and number of iterations to T (in general, D>log2N)$ D>\text{log}_{2}N)$. Based on current literature [33], the time complexity of the basic SSA is given by. OSSA(Tfalse(NDfalse))$$\begin{equation} {O_{\text{SSA}}}(T(N*D)) \end{equation}$$…”
Section: Prediction Modelmentioning
confidence: 99%